2021
DOI: 10.1080/1034912x.2021.1917525
|View full text |Cite
|
Sign up to set email alerts
|

Education of Children with Disabilities in Rural Indian Government Schools: A Long Road to Inclusion

Abstract: Global commitments to the education of children with disabilities, have led to progressive policy developments in India, and a surge in the enrolment of children who were traditionally excluded from the formal education system. This paper examines the perceptions and practices of mainstream teachers in rural government schools, within the context of increased learner diversity, focusing on how teachers understand, and respond to, the needs of children with disabilities. Data were collected through semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…This study and others have found that attending school or even progressing to higher grades may not be indicative of children with disabilities’ learning (Banks et al 2019 ; Singal 2008 ). Whilst the quality of education is an issue for all children, children with disabilities appear more likely to be excluded from the learning process because of the lack of inclusive education provisions, including teacher training and specialist resources (Chitiyo et al 2015 ; Jolley et al 2018 ; Mkandawire, Maphale & Tseeke 2016 ; Taneja-Johansson et al 2021 ). In the study areas, less than 2% of primary school classrooms had any inclusive education resources (MoEM 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study and others have found that attending school or even progressing to higher grades may not be indicative of children with disabilities’ learning (Banks et al 2019 ; Singal 2008 ). Whilst the quality of education is an issue for all children, children with disabilities appear more likely to be excluded from the learning process because of the lack of inclusive education provisions, including teacher training and specialist resources (Chitiyo et al 2015 ; Jolley et al 2018 ; Mkandawire, Maphale & Tseeke 2016 ; Taneja-Johansson et al 2021 ). In the study areas, less than 2% of primary school classrooms had any inclusive education resources (MoEM 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of challenges can create barriers to educational inclusion, participation and attainment amongst children with disabilities, including inaccessible school facilities and transport to schools, inadequate teacher skills in inclusive education, caregiver and teacher attitudes and lack of resources to support inclusive education (Banks et al 2019 ; Singal et al 2015 ; Taneja-Johansson, Singal & Samson 2021 ; United Nations 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] A 0.18 standard deviation reduction in test scores was, therefore, equal to a 3.6% loss in future income for each year a child suffered MSVI while in school. For blind children, we assumed that they did not go to school, or learned minimally,[ 23 ] experiencing a reduction in future income equivalent to reported returns to 1 year of schooling from primary school education – 5.5%. [ 24 ] 1* Future incomes were proxied by the stream of future GDP per capita, estimated using the time series of GDP (growth), and population growth rates (middle-of-the-road scenario) from the Shared Socioeconomic Pathways database by the International Institute for Applied Systems Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This paper provides some preliminary results from the DIVERSASIA project, which focuses on inclusive HE in India and Bangladesh. There, too, inclusive education is thought about more at the general level than at the HE level (Ambia & Rahman, 2021;Fayaz, 2019;Singal, 2019;Taneja-Johansson et al, 2021). In HE, change happens rather slowly.…”
Section: Introductionmentioning
confidence: 99%